2020
DOI: 10.1002/ajp.23093
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive measurement of mucosal immunity in a free‐ranging baboon population

Abstract: Ecoimmunological patterns and processes remain understudied in wild primates, in part because of the lack of noninvasive methods to measure immunity. Secretory immunoglobulin A (sIgA) is the most abundant antibody present at mammalian mucosal surfaces and provides an important first line of defense against pathogens. Recent studies show that sIgA can be measured noninvasively in feces and is a good marker of mucosal immunity. Here we validated a commercial ELISA kit to measure fecal IgA in baboons, tested the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 96 publications
(210 reference statements)
0
17
1
Order By: Relevance
“…The combined extract was finally centrifuged for 5 min at 2000 g , the supernatant was transferred into a polypropylene tube, and samples were stored at −20°C until IgA analysis. Different from Gesquiere et al (2020), we added a second extraction step after we found in an initial experiment on a subset of 18 samples that re‐extraction increased IgA concentrations on average by 42% (range 32%–54%). In addition to improving overall extraction efficiency (c.f.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The combined extract was finally centrifuged for 5 min at 2000 g , the supernatant was transferred into a polypropylene tube, and samples were stored at −20°C until IgA analysis. Different from Gesquiere et al (2020), we added a second extraction step after we found in an initial experiment on a subset of 18 samples that re‐extraction increased IgA concentrations on average by 42% (range 32%–54%). In addition to improving overall extraction efficiency (c.f.…”
Section: Methodsmentioning
confidence: 99%
“…In 340 fecal extracts, IgA was measured using the commercial monkey IgA ELISA kit (Life Diagnostics, Inc., Cat# IGA‐3) previously used for IgA assessment in fecal samples of baboons (Gesquiere et al, 2020). For measurement, all extracts were diluted 1:20 with assay diluent provided by the kit, and samples were measured in duplicate according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, epidemiological evaluation of STH burden in human populations shows that in endemic areas, infected individuals suffer chronic parasitism throughout their lives (79)(80)(81)(82). This holds true for non-human primates (83)(84)(85), livestock (86,87), and wild rodent populations (88,89). In humans, infection burden correlates strongly with age following one of two patterns: (i) parasite burden builds rapidly during early childhood but peaks shortly before adolescence, burden then declines and plateaus at a low level throughout adulthood e.g., Trichuris trichiura, and Ascaris lumbricoides (79,90,91); or (ii) STH burden builds consistently throughout childhood and early adolescence but plateaus at a moderate level prior to adulthood e.g., Necator americanus and Ancylostoma duodenale (82).…”
Section: Natural Sth Infection In Mammalsmentioning
confidence: 99%